American Dog : Star - Shotz, Jennifer Li (New York, NY : Alloy Entertainment, 2020)
"After her elderly owner passes away, Star--a deaf Australian shepherd--is brought to a local shelter. Star feels scared and alone--until she meets twelve-year-old Julian. After getting in trouble at school yet again, Julian volunteers at the shelter and realizes he can communicate with Star in a way that no one else can. Their bond continues to grow, and Julian and Star become inseparable. Then the unthinkable happens: Funding for the shelter dries up. The only way to save Star is to adopt her, but he has to prove that he can stay out of trouble and train a dog like Star. Will Julian and Star find a way to stay together forever?"--Back cover.
Keywords: Dogs -- Juvenile fiction; Deaf dogs -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Friendship -- Juvenile fiction; Animal shelters -- Juvenile fiction; Juvenile fiction